PERTUMBUHAN KULTUR TUNAS AKSILAR KENTANG (Solanum tuberosum L.) DENGAN PENAMBAHAN SUPER FOSFAT DAN KNO3 PADA MEDIA AB MIX SECARA IN VITRO - Hamami Alfasani Dewanto; Desi Saraswati; Oetami Dwi Hadjoeningtijas (Universitas Muhammadiyah Purwokerto, 2018)
Murashige&Skoog-based medium Potatoes are one commodity that has the potential to be developed as a resource in the context of food diversification, farmers' income riser, non fossil export commodities and raw materials for processing industry. The objective of this research was to find out the effect of SP-36 fertilizer, KNO3 fertilizer, as well as the interaction between the two fertilizers on the growth of potato nodal culture on AB Mix media in vitro. The results of this study are expected to provide economical potato tissue culture media development. This research used factorial complete randomized design. The treatment were SP-36 concentration: 0 ppm; 50 ppm; 100 ppm; and 200 ppm, in combination with KNO3 concentration: 0 ppm; 100 ppm; 200 ppm; 400 ppm; and 600 ppm, The variables observed included number of leaves, leaf color, length of plantlets, fresh weight of plantlets and percentage of plantlets growth. Based on the results of the analysis of variance (ANOVA) F. Calculate < F. Table with the average success of plantlet growth between 87.5-100%. In addition, there are four types of leaf color produced, namely the color of yellowish green, pale green leaves, green, and dark green. Research showed that the interaction between SP-36 fertilizer and KNO3 fertilizer on AB Mix media had no significant effect on all observed variables.